2014
DOI: 10.6018/analesps.30.1.139251
|View full text |Cite
|
Sign up to set email alerts
|

Modelos cognitivos del desarrollo de las funciones ejecutivas. Limitaciones metodológicas y desafíos teóricos.

Abstract: Título: Modelos cognitivos del desarrollo de las funciones ejecutivas. Limitaciones metodológicas y desafíos teóricos. Resumen: Las funciones ejecutivas (EF) han sido definidas como una serie de procesos cognitivos de orden superior, que permiten el control del pensamiento, comportamiento y afectividad conforme al logro de una meta. Tales procesos presentan un desarrollo posnatal prolongado, culminando su maduración sobre el final de la adolescencia. En el presente artículo se realiza una revisión de algunos d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 94 publications
1
3
0
5
Order By: Relevance
“…The finding on the age coincides with the development of this ability during primary school ( Ferrer et al, 2009 ). The data on the contribution of perceptual inhibition coincide with the results of previous studies in children (e.g., Stelzer, 2014 ), and they are in line with those theoretical proposals that suggest that the ability to control interference at a perceptual level take part in the operations involved in FI (e.g., Dempster & Corkhill, 1999 ; McCall, 1994 ; McCall & Carriger, 1993 ; Stelzer, 2014 ). In this sense, inhibitory control at a perceptual level would promote the attentional focus on those elements that are relevant to the resolution of new problems, acting as the first process of voluntary control in the processing of information.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The finding on the age coincides with the development of this ability during primary school ( Ferrer et al, 2009 ). The data on the contribution of perceptual inhibition coincide with the results of previous studies in children (e.g., Stelzer, 2014 ), and they are in line with those theoretical proposals that suggest that the ability to control interference at a perceptual level take part in the operations involved in FI (e.g., Dempster & Corkhill, 1999 ; McCall, 1994 ; McCall & Carriger, 1993 ; Stelzer, 2014 ). In this sense, inhibitory control at a perceptual level would promote the attentional focus on those elements that are relevant to the resolution of new problems, acting as the first process of voluntary control in the processing of information.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning perceptual inhibition, some studies analyzed its relationship with FI. Stelzer (2014) found that perceptual inhibition (along with working memory and planning) predicts the FI performance in children from 79 to 89 months, while Zhao and Jia (2018) did not find effects on FI after a training on perceptual inhibition in children from 10 to 12 years old.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…There is substantial theoretical overlap between these processes and shared variance in the tasks that tap them (Stelzer et al, 2014). For example, Best and Miller (2010) place the well- researched Dimensional Change Card Sort (DCCS) task squarely in the domain of complex behavioral inhibition whereas Garon et al (2008) classify it as a set-shifting task.…”
Section: Introductionmentioning
confidence: 99%
“…1) modelos de constructo unitario, 2) modelos de una estructura formada por componentes independientes y, 3) modelos de componentes disociables en una estructura integrada (Stelzer, Mazzoni y Cervigni, 2014).…”
Section: Modelos Teóricos De Las Funciones Ejecutivasunclassified